129 Pilot study: the validity of the queens square screening test for visual deficits in a cohort of patients with dementia. (29th July 2019) - Kim, Leah; Cordato, Dennis; McDougall, Alan; Fraser, Clare
Abstract : Introduction: There is limited research on the visual deficits found in dementia. The Queens Square Screening Test for Visual Deficits (QS test) is designed to screen for changes in visual processing. Our study aimed to validate this test and examine the types of visual processing deficits found in dementia. Methods: We assessed the QS test in participants with dementia, mild cognitive impairment (MCI), and healthy controls. Participants were recruited from the Neurology and Geriatrics departments of a tertiary hospital over 3-months. Cognitive impairment was measured using the Rowland Universal Dementia Assessment Scale (RUDAS). Results: Twenty-six patients were examined. There were no statistically significant differences in age, gender, English fluency, and education between the three groups. Participants with dementia (n=8, mean RUDAS 17.5/30) scored 51.4/71 on the QS test, compared to 60.7/71 in MCI (n=7, mean RUDAS 25.0/30) and 64.6/71 in controls (n=11, mean RUDAS 27.4/30). The mean scores for each subset of the QS test for dementia, MCI and normal cognition, respectively, were: early visual processing – 19.6/25, 22.4/25, 23.7/25; object perception – 5.6/11, 7.9/11, 8.7/11; space perception – 11.4/14, 11.1/14, 12.4/14; face perception – 4.4/8, 6.4/8, 7.0/8; reading – 10.4/13, 12.9/13, 12.8/13. Conclusion: In this pilot study, the QS test was markedly abnormal in dementia but did not differentiate between MCI and normal cognition. Our findings suggest that deficits in early visual processing, reading, and the perception of objects and faces are common in dementia. Understanding the types of visual difficulties may improve the care of patients with dementia.